Expression of β-catenin in external auditory canal cholesteatoma (EACC) - Naim, Ramin; Riedel, Frank; Bran, Gregor M.; Hörmann, Karl (Biofactors, 2003)
External auditory canal cholesteatoma (EACC) is a chronic inflammation of the external auditory canal and is composed of hyperproliferative epithelium. The upward migration of the epithelial cells requires permanent breakdown and reformation of intercellular connection. This is established by the modulation of the adherent junctions consisting of an E-Cadherin-β-catenin complex. Dissociated β-catenin intranuclearly enables persistent activation of downstream transcription and growth factors and decreases the integrity of tissue. In our study we examined EACC and normal meatal auditory skin taken from 16 patients between 23 and 74 years of age. Immunostaining for β-catenin was used for semiquantitative description of the specimens after assessing hematoxylin-eosin-stained slides. β-catenin was expressed in all layers of AMS-epithelium, whereas in EACC only basal layer of the matrix epithelium showed positive immunostaining for β-catenin. In the suprabasal layer of the epithelium only faint reactivity was detectable. The immunostaining was restricted to the membrane of the cells. We assumed that either the content of membranous β-catenin was decreased or β-catenin was changed due to molecular modification. It is known that stimulation of endothelial cells by certain growth factors, β-catenin is maximally phosphorylated. In regard to the increased loss of immunoreactivity for β-catenin in the suprabasal layers of the hyperplastic EACC-matrix, we assumed bio-molecular modification or loss of β-catenin decreasing the cell-cell-integrity. Furthermore, this might result in desquamation of keratinocytes and accumulation of dead keratin debrids. In sum, this study should be understood as a descriptive analysis of β-catenin expression in EACC.